Transformational Leadership of the Regent of West Bandung for the 2022-2023 Period in Post-Pandemic Economic Recovery - Rivaldi Rivaldi; Dede Sri Kartini; Neneng Yani Yuningsih (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to analyze the transformational leadership of the West Bandung Regent for the 2022–2023 period in the context of community economic recovery after the pandemic. Transformational leadership with four main dimensions, namely ideal influence, inspirational motivation, intellectual stimulation, and individual consideration is used as an analytical framework to see the extent to which leadership style can encourage economic recovery in a participatory, innovative, and inclusive manner. The research method used is qualitative with a descriptive-analytical approach. Data collection techniques are carried out through documentation and in-depth interviews with informants from government, academics, business actors, media, and the community. Data analysis techniques are carried out thematically and inductively to trace the meaning of leadership actions and their impact on program implementation. The results of the study show that the Regent's leadership reflects a transformational character. The ideal influence dimension is seen in the courage to directly lead the economic assistance program. Inspirational motivation is reflected in the vision of regional development that drives community participation. Intellectual stimulation is realized through digital-based entrepreneurship training. Individual consideration is seen in dialogue activities with business actors at the local level. This leadership is able to improve bureaucratic performance and community involvement in economic programs. However, equal access to assistance and minimal business assistance are still obstacles. The conclusion of this study is that transformational leadership plays an important role in rebuilding the regional economy and needs to be further developed by strengthening the evaluation system and distributing information evenly throughout the region.